Evaluasi Kualitas Informasi Obat Pada Brosur Obat - Nopratilova; Eksanti Indriani Sabila; Dedi Nugroho; Rizky Farmasita Budiastuti; Alhara Yuwanda; Anugerah Budipratama Adina (Jurnal Sains Farmasi Dan Kesehatan, 2024)
The research aims to describe the information in drug brochures. Classification of drug brochures: categorization of drugs based on labeling, name, product origin and therapeutic class. The study also assesses the completeness of information in drug brochures, following Indonesian Ministry of Health regulations (Number: 386/MENKES/SK/IV/1994), Indonesian National Agency of Drug and Food Control (BPOM) regulations (Number 2 of 2021) and WHO Ethical Criteria for Medicinal Drug Promotion in 1988. This descriptive study uses simple random sampling with a sample size of 30 drug brochures. Research findings for drug brochures: Classification of drugs based on labeling shows that 33.3% are over-the-counter drugs, 46.7% are prescription-only drugs and 20.0% are classified as hard drugs. Based on the name, 100.0% are branded drugs. The product origin reveals that 100.0% are domestically manufactured drugs. The most common therapeutic class is Analgesics & Antipyretics is 20.0%. The completeness of information in drug brochures according to the criteria specified in Indonesian Ministry of Health regulations (Number: 386/MENKES/SK/IV/1994) is 50.0%, for BPOM regulations (Number 2 of 2021) is 20.0% and for WHO Ethical Criteria for Medicinal Drug Promotion in 1988 is 20.0%.